KAJIAN PENGGUNAAN BAHAN PEMUCAT TERHADAP KUALITAS MINYAK GORENG BEKAS KERIPIK BUAH (Jurnal Teknologi Pangan, 2013)
Cooking  oil  is  one  of  nine  basic  commodities  needed  by  society.  Disruption  of continuity of supply of products will greatly affect the prices and caused upheavals that are not desired. Various means of oil production, from how to do simple home industry through the use of technology and high costs that can only be done by big industry. On the  use  of cooking  oil or  multiple  times, for  example in fruit frying chips, potato chips,  etc., which will cause  deterioration  in quality caused by the  heating  process with high temperature  which  would  result  in  physical  or  chemical  changes  such  as  blackish  color, embossed froth , the  smell  of burning, longer frying  time and rancid odor that would restrict the use of cooking oil. Bleaching using a 7% weight mixture of active carbon and bleaching earth / bleaching earth (1: 3) gives the results of fruit chips used frying oil with color appearance closer to a new cooking oil.Keywords: bleaching, used frying oil